2020
DOI: 10.3390/geosciences10030086
|View full text |Cite
|
Sign up to set email alerts
|

n-Alkane Distribution—A Paleovegetation Change Indicator during the Period from Late Glacial to Late Holocene on Russian Plain (Bryansk Region)

Abstract: Loess-paleosol series are well preserved in the south part of the Russian Plain. However, these sequences have a low number of studies on their organic matter, such as researches of isotope composition, n-alkane and other biomarkers. Thus, the purpose of the study was to reconstruct vegetation conditions from the Late Glacial to Late Holocene. We used the leaf wax-derived n-alkanes to detect vegetation evolution of the Bryansk Region. The stable carbon isotope composition of organic matter and pedogenic carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Odd C-number 1.00-4.80 [42] Pichavaram mangroves, India n-C11-n-C37 Various 0.75-8.63 [40] Central Alaska, USA n-C19-n-C35 Odd C-number 2.20-21.00 [38] Suez Gulf, Egypt n-C10-n-C40 Mainly even C-number 0.62-1.95 [43] Lake Middle Marviken, Sweden n-C15-n-C31 Odd C-number 3.60-8.00 [39] Banja Luka, Bosnia and Herzegovina n-C14-n-C39 Odd C-number 1.12-1.48 This study of C atoms, an anthropogenic source of pollution in all samples can be confirmed [17,22,23]. Based on previous findings, this leads to the conclusion that the samples contain an organic substance of native origin with intensive input from anthropogenic sources.…”
Section: N-c17-n-c36mentioning
confidence: 99%
“…Odd C-number 1.00-4.80 [42] Pichavaram mangroves, India n-C11-n-C37 Various 0.75-8.63 [40] Central Alaska, USA n-C19-n-C35 Odd C-number 2.20-21.00 [38] Suez Gulf, Egypt n-C10-n-C40 Mainly even C-number 0.62-1.95 [43] Lake Middle Marviken, Sweden n-C15-n-C31 Odd C-number 3.60-8.00 [39] Banja Luka, Bosnia and Herzegovina n-C14-n-C39 Odd C-number 1.12-1.48 This study of C atoms, an anthropogenic source of pollution in all samples can be confirmed [17,22,23]. Based on previous findings, this leads to the conclusion that the samples contain an organic substance of native origin with intensive input from anthropogenic sources.…”
Section: N-c17-n-c36mentioning
confidence: 99%
“…Ghosh et al, 2006; Lu et al, 2007; Reitz and Shackley, 2012; Revelles et al, 2016). Similarly, organic geochemical proxies, such as total organic carbon (TOC) to total nitrogen (N) ratio (C/N), stable isotopes of organic carbon (δ 13 C) and lipid biomarkers have been used in archaeological research (Aichner et al, 2018; Boutton et al, 1998; Eckmeier and Wiesenberg, 2009; Stolpnikova et al, 2020). The proxies are primarily used for identifying the source (e.g.…”
Section: Introductionmentioning
confidence: 99%